Tool wear monitoring in belt grinding process based on thermal signatures - Wijaya, Jonathan (2018)
In machining, major factors that affect the surface roughness or surface topography are machine tool vibrations, tool tip/chip temperature and tool wear condition along with machining parameters like cutting speed, feed rate, depth of cut, tool geometry. So it becomes important for the manufacturing industry to find the suitable levels of process parameters for obtaining maintaining tool life. Heat generation in machining is always a topic to be studied as it correlates with the interaction with tool and workpiece. The aim of this report is to understand tool wear monitoring for belt grinding operation based on thermal signatures. By sensing the belt wear in real time during the robotic abrasive belt grinding process, the author could investigate the relationship of the abrasive belt tool life with the temperature measured. This experiment presented in this report were conducted using a customized tribometer imparting a constant normal force to the aluminium plate fixed on a translational slider. Abrasive belt of grit size 60 in two different wear states was tested. Abrasive belt sample was attached into the tribometer where the constant contact normal force was directly applied to the surface of the plate during the scratching experiment. In this report, the authors have used the thermopile and thermal imaging camera as the measurement devices. The results of the experiments conducted, display that in the new belt condition, higher temperature signatures were observed whereas in old belt condition lower thermal signatures occur. These findings of the correlation between the belt condition and the temperature signature play a significant factor in assessing the abrasive tool performance. Performing these thermal tests periodically can aid in the prediction of service life for things. Furthermore, these findings help on grinding industry to develop on the efficiency of the belt for the maximum usage and thus saving the abrasive belt cost without damaging the workpiece surface.